Quality Monitoring for a Water Reclamation System in a Mandarin Orange Canning Factory - Wu, D.; chu, Y.; Chen, J.; Hong, J.; Gao, H.; Fang, Zhongxiang; Shen, L.; Lin, M.; Liu, D.; Ye, X. (Taylor & Francis Ltd., 2013)
To conserve water in the mandarin orange canning industry, a water reclamation system was designed for a production scale of 50 kL/h. The discharged water from mandarin transportation using a conveyor belt was collected in a pool, chlorinated, filtered by active carbon, and then UV-sterilized. This water was then reused for the processes of segmenting, transportation, and washing after alkaline solution treatment. The water quality had been monitored during the water reclamation. The results showed that the reused water quality was improved by the system and the main physicochemical properties and sensory index were conformed to the requirements of Chinese National Standard GB5749 except the index of chemical oxygen demand. The reused water contained about 0.4 ppm of chlorine and 10 μg/mL of pectin. The total bacterial count was ≤10CFU/mL and no Escherichia coli was detected. The seasonal production monitoring results showed that the quality of disposed water from this system remained stable. This technology might be useful for water reclamation in other fruit processing plants.